2018
DOI: 10.1016/j.chom.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The Marburgvirus-Neutralizing Human Monoclonal Antibody MR191 Targets a Conserved Site to Block Virus Receptor Binding

Abstract: Summary Since its first identification 50 years ago, Marburgviruses have emerged several times, with 83–90% lethality in the largest outbreaks. Although no vaccines or therapeutics are available for human use, the human antibody MR191 provides complete protection in nonhuman primates when delivered several days after inoculation of a lethal marburgvirus dose. The detailed neutralization mechanism of MR191 remains outstanding. Here we present a 3.2 Å crystal structure of MR191 complexed with a trimeric marburgv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 55 publications
(84 reference statements)
1
62
0
Order By: Relevance
“…This is likely due to a combination of a clash with the recently described MARV wing anchor at the base of the GP (King et al, 2018) (Figure S4A), as well as sequence divergence at the critical contact residue Q560, which is an arginine (R561) in MARV, a bulkier residue that likely clashes with the CDRH3(Figure S4B). It has been demonstrated that the MLDs hang over the sides of the MARV GP, in contrast to their conformation in ebolaviruses, which possibly further shields the ADI-15878 epitope in marburgviruses (Hashiguchi et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…This is likely due to a combination of a clash with the recently described MARV wing anchor at the base of the GP (King et al, 2018) (Figure S4A), as well as sequence divergence at the critical contact residue Q560, which is an arginine (R561) in MARV, a bulkier residue that likely clashes with the CDRH3(Figure S4B). It has been demonstrated that the MLDs hang over the sides of the MARV GP, in contrast to their conformation in ebolaviruses, which possibly further shields the ADI-15878 epitope in marburgviruses (Hashiguchi et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…We also modeled a large portion of HR2 down to residue 625 (Figure 2A), which adopts a three-helix bundle within the GP2 and has been previously modeled for EBOV/May (Zhao et al, 2016) and MARV (King et al, 2018). Notably, HR2in MARV is slightly different from the ebolaviruses, with a slightly wider three-helix bundle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations